21st Century ELT Skills Impact in Students-Teachers Language Learning Process Enhancement - Garcia Mosquera, Maria Fernanda (Coloquio, 2023)
The article addresses a reflective-argumentative text on the 21st century languagelearning skills significance in the educational process. The study links the paramountoutcomes of monitoring techniques, effective communication, and information literacyincluded in the second-language acquisition by characterizing the advantages of distinctivecompetencies. Data were retrieved through a bibliographic revision. Findings corroboratedthat the enjoyment of proper capabilities in the current era constitutes an outstanding factor inthe educational process. As a concluding point, it is pivotal to understand the prominentrelation between the innovative trends in teaching propensities and the competences of aproactive individual in the present time.